A Rice Autophagy Gene OsATG8b Is Involved in Nitrogen Remobilization and Control of Grain Quality - Fan, Tian; Yang, Wu; Zeng, Xuan; Xu, Xinlan; Xu, Yanling; Fan, Xiaorong; Luo, Ming; Tian, Changen; Xia, Kuaifei; Zhang, Mingyong (Frontiers in Plant Science, 2020)
Enhancing nitrogen (N) use efficiency is a potential way to reduce excessive nitrogen application and increase yield. Autophagy is a conserved degradation system in the evolution of eukaryotic cells and plays an important role in plant development and stress response. Autophagic cores have two conjugation pathways that attach the product of autophagy-related gene 8 (ATG8) to phosphatidylethanolamine (PE) and ATG5 to ATG12, respectively, which then help with vesicle elongation and enclosure. Rice has six ATG8 genes, which have not been functionally confirmed so far. We identified the rice gene OsATG8b and characterized its role in N remobilization to affect grain quality by generating transgenic plants with its over-expression and knockdown. Our study confirmed the autophagy activity of OsATG8b through the complementation of the yeast autophagy-defective mutant scatg8 and by observation of autophagosome formation in rice. The autophagy activity is higher in OsATG8b-OE lines and lower in OsATG8b-RNAi than that in wild type (ZH11). 15N pulse-chase analysis revealed that OsATG8b-OE plants conferred higher N recycling efficiency to grains, while OsATG8b-RNAi transgenic plants exhibited lower N recycling efficiency and poorer grain quality. The autophagic role of OsATG8b was experimentally confirmed, and it was concluded that OsATG8b-mediated autophagy is involved in N recycling to grains and contributes to the grain quality, indicating that OsATG8b may be a potential gene for molecular breeding and cultivation of rice.